Modelling duodenum radiotherapy toxicity using cohort dose-volume-histogram data. Issue 3 (June 2017) - Holyoake, Daniel L.P.; Aznar, Marianne; Mukherjee, Somnath; Partridge, Mike; Hawkins, Maria A.
Abstract: Background and purpose: Gastro-intestinal toxicity is dose-limiting in abdominal radiotherapy and correlated with duodenum dose-volume parameters. We aimed to derive updated NTCP model parameters using published data and prospective radiotherapy quality-assured cohort data. Material and methods: A systematic search identified publications providing duodenum dose-volume histogram (DVH) statistics for clinical studies of conventionally-fractionated radiotherapy. Values for the Lyman-Kutcher-Burman (LKB) NTCP model were derived through sum-squared-error minimisation and using leave-one-out cross-validation. Data were corrected for fraction size and weighted according to patient numbers, and the model refined using individual patient DVH data for two further cohorts from prospective clinical trials. Results: Six studies with published DVH data were utilised, and with individual patient data included outcomes for 531 patients in total (median follow-up 16 months). Observed gastro-intestinal toxicity rates ranged from 0% to 14% (median 8%). LKB parameter values for unconstrained fit to published data were: n = 0.070, m = 0.46, TD50(1) [Gy] = 183.8, while the values for the model incorporating the individual patient data were n = 0.193, m = 0.51, TD50(1) [Gy] = 299.1. Conclusions: LKB parameters derived using published data are shown to be consistent to those previously obtained using individual patient data, supporting a small volume-effect and dependence on exposure to high threshold dose.